Super-hydrophobic wood, preparation method thereof and composite suspension

Through alkali etching treatment and nano-hydroxyapatite composite suspension, combined with the low surface energy of PDMS, the problems of expensive wood modification equipment and poor coating stability in the prior art are solved, and the efficient and durable ultra-hydrophobic wood is achieved. and self-healing effects, suitable for outdoor applications.

CN119283143AActive Publication Date: 2025-01-10FUJIAN AGRI & FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411404601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The prior art When modifying wood, there are expensive equipment, complex operation, high cost, difficult to treat the substrate surface with large areas or complex shapes, and poor stability of superhydrophobic coating, which is susceptible to mechanical damage or chemical corrosion, and cannot be effectively applied to wood. The chord section is not easy to recover.

Method used

Alkaline etching treatment combined with nano-hydroxyapatite and polydimethylsiloxane composite suspension to form a stable superhydrophobic wood coating, which enhances surface roughness and attachment through the low surface energy of PDMS and the micro-nano structure of HAP Focus on achieving self-healing and long-term stability of the coating.

Benefits of technology

It significantly improves the superhydrophobicity and self-cleaning effect of wood. The coating remains stable in a variety of environments and has good self-repair capabilities. It is suitable for outdoor applications and maintains the mechanical properties of wood, reducing the potential for the environment and human body. harm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005076180880000011
    Figure HDA0005076180880000011
  • Figure HDA0005076180880000012
    Figure HDA0005076180880000012
  • Figure HDA0005076180880000021
    Figure HDA0005076180880000021
Patent Text Reader

Abstract

The invention relates to the field of wood functional materials, and discloses super-hydrophobic wood, a preparation method thereof and composite suspension liquid. The composite suspension comprises the following components: nano-hydroxyapatite, polydimethylsiloxane, ethyl acetate and a curing agent. The preparation method of the super-hydrophobic wood comprises the following steps: carrying out alkali etching treatment on the wood; and the composite suspension liquid is sprayed on the surface of wood, and the super-hydrophobic wood is obtained after curing. The prepared super-hydrophobic wood has excellent water repellency, the water contact angle of the super-hydrophobic wood can reach 153.3 degrees, meanwhile, the rolling angle is small and is only 4.3 degrees, and the super-hydrophobic wood is suitable for being applied to wood in the outdoor environment. After the coating is exposed outdoors for 60 days, the water contact angle can still be kept at 152.5 degrees, and the rolling angle is about 6.1 degrees, so that the coating is proved to have good weather resistance. And after multiple wear repair cycles, the water contact angle can still be recovered to 142 degrees, and the repair rate is as high as 92.4%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wood functional materials, and more specifically to super-hydrophobic wood and a preparation method and a composite suspension thereof. Background Art

[0002] Wood is one of the most abundant biomaterials in the world. It has the advantages of high mechanical strength and strong degradability. It is widely used in furniture, construction and other fields. However, due to the porous structure and hydrophilic groups of wood itself, it is easy to absorb water in a humid environment, prone to deformation and a series of problems, which seriously affect the durability of wood products. In order to solve this problem, people have proposed to modify wood to be super-hydrophobic, reduce the hydrophilicity of wood, reduce the cracking and deformation caused by shrinkage and swelling, and thus extend the service life of wood products.

[0003] At present, the existing research methods mainly introduce inorganic nanoparticles on the wood surface and construct micro-nano rough structures through impregnation, in-situ generation and other methods, and then achieve superhydrophobic modification by modifying low surface energy materials. Although these methods have been effective in improving the hydrophobic properties of wood, they still face several challenges: the preparation process is complicated and the cost is high, making it difficult to achieve industrial production; some treatment materials are biologically toxic and have adverse effects on the environment or human body; most methods can only achieve superhydrophobic modification on the cross section of wood, while the tangential section of wood is more exposed in actual use, but the existing technology is difficult to apply on this surface. In addition, the existing superhydrophobic coatings have poor stability and are easily affected by mechanical damage or chemical corrosion, causing them to lose their waterproof properties.

[0004] Prior art CN201510260258.X coats vinyl triethoxysilane and nanoparticles on the wood surface by vapor deposition to prepare super-hydrophobic wood. However, the vapor deposition method not only requires expensive equipment, complicated operation, and high cost, but also cannot be applied to large-area or complex-shaped substrate surfaces, and the deposition speed is slow and time-consuming. The resulting super-hydrophobic wood is not suitable for outdoor use and is not easy to recover after the coating is damaged.

[0005] Therefore, there is an urgent need for a simple, low-cost, long-lasting superhydrophobic modification method that can be applied to the tangential section of wood to improve the durability of wood and broaden its application range in practical environments. Summary of the invention

[0006] The present invention provides a super-hydrophobic wood to overcome the defects of the prior art, such as expensive equipment, complicated operation, high cost, inability to form a large-area or complex-shaped substrate surface, long preparation time, and difficulty in recovering the coating after being damaged.

[0007] Another object of the present invention is to provide a method for preparing super-hydrophobic wood;

[0008] Another object of the present invention is to provide a composite suspension.

[0009] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0010] A method for preparing super-hydrophobic wood comprises the following steps:

[0011] S1: alkaline etching treatment of wood;

[0012] S2: A composite suspension containing nano-hydroxyapatite (HAP), polydimethylsiloxane (PDMS), ethyl acetate and a curing agent is treated on the wood surface, and superhydrophobic wood is obtained after curing.

[0013] The present invention innovatively uses PDMS with good flexibility on the wood surface to form a uniform, continuous film on the wood surface. The super-hydrophobic wood coating prepared by the present invention can withstand a certain degree of mechanical damage without being prone to cracking or peeling when the wood is stressed, deformed or subjected to external impact. PDMS enables the super-hydrophobic wood of the present invention to repair minor damage through rearrangement and migration of molecular chains, so that the super-hydrophobic coating can be repaired multiple times, significantly extending the service life and effectiveness of the coating.

[0014] The present invention innovatively utilizes the inorganic properties of HAP, and its wood surface has high stability and will not degrade or undergo significant chemical changes under various environmental conditions. The surface of HAP is rich in hydroxyl groups, which can provide active sites for binding with PDMS molecules. On the wood surface treated with alkali etching, HAP nanoparticles can form stronger physical adsorption or chemical bonding with the active sites of wood (such as hydroxyl groups exposed on the wood surface) through the hydroxyl groups on their surface, thereby enhancing the adhesion and stability of the PDMS coating.

[0015] At the same time, the micro-nanostructure of HAP particles increases the surface roughness, while PDMS as a low surface energy material further reduces the interaction between water and the surface. This synergistic effect not only increases the surface contact angle, but also makes the coating more stable and durable.

[0016] Preferably, the polydimethylsiloxane is a polydimethylsiloxane prepolymer.

[0017] Preferably, the nano-hydroxyapatite is hydroxyapatite nanospheres with a diameter of 10 to 100 nm.

[0018] Preferably, the mass ratio of the curing agent to the polydimethylsiloxane prepolymer is 1:10.

[0019] Preferably, the curing agent includes a condensation type curing agent and an addition reaction type curing agent, including ethoxysilane, methoxysilane, and silicon hydrogen siloxane.

[0020] Preferably, the composite suspension is sprayed on the wood surface at a distance of 30 to 50 cm from the wood surface.

[0021] Preferably, the curing temperature in S2 is 20°C to 150°C.

[0022] Preferably, the curing in S2 can be carried out at room temperature (20° C. to 25° C.).

[0023] Preferably, the curing time in S2 is 0.1 to 12 hours.

[0024] Furthermore, the mass ratio of ethyl acetate to nano-hydroxyapatite is 400-600:1.

[0025] Preferably, the mass ratio of ethyl acetate to nano-hydroxyapatite is 500:1.

[0026] Furthermore, in the composite suspension described in S2, the mass ratio of nano-hydroxyapatite to polydimethylsiloxane prepolymer is 1:8-20.

[0027] Preferably, in the composite suspension described in S2, the mass ratio of nano-hydroxyapatite to polydimethylsiloxane prepolymer is 1:10-15.

[0028] Furthermore, during the alkali etching treatment in S1, the wood is immersed in an alkali solution with a concentration of 0.1 to 1 wt%.

[0029] Preferably, the concentration of the alkaline solution is 0.5 wt %.

[0030] Furthermore, during the alkali etching treatment in S1, the wood is immersed in an alkali solution for 1 to 2 hours.

[0031] Preferably, the soaking time is 2 hours.

[0032] Preferably, after the alkali solution immersion is completed, the wood surface is cleaned with deionized water and dried at 25-103°C.

[0033] Furthermore, the amount of the composite suspension in S2 added to the wood surface is 0.8-1.2 g / cm 2 .

[0034] Preferably, the composite suspension is sprayed on the wood surface at a distance of 30 to 50 cm from the wood.

[0035] Furthermore, the wood surface in S2 includes a cross section, a tangential section and a radial section.

[0036] A super-hydrophobic wood is prepared by the preparation method.

[0037] Furthermore, after being damaged, the super-hydrophobic coating can be restored at a temperature above 80°C and below 120°C.

[0038] Preferably, recovery is at 100°C.

[0039] A composite suspension is used for preparing the super-hydrophobic wood, and its components include nano-hydroxyapatite, polydimethylsiloxane, ethyl acetate and a curing agent.

[0040] Preferably, the composite suspension can be applied to the wood surface including the cross section, tangential section and radial section.

[0041] Preferably, the composite suspension is prepared by the following method: adding nano-hydroxyapatite to ethyl acetate, then adding polydimethylsiloxane and a curing agent, and dispersing them to obtain a composite suspension.

[0042] The present invention constructs a stable superhydrophobic system on the wood tangential section through the dual mechanisms of alkali etching treatment and composite coating. Alkaline etching treatment provides basic roughness and active sites, while HAP nanoparticles further enhance the surface micro-nano structure, and the low surface energy of PDMS effectively reduces the hydrophilicity of the surface. The combination of the two allows water droplets to form a high contact angle on the wood surface and a very small rolling angle, achieving excellent superhydrophobicity and self-cleaning effects.

[0043] When the coating is worn, PDMS is thermoresponsive and can reflow and cover the damaged area under heating conditions. HAP, as a stable nanoparticle, provides a support framework that allows PDMS to quickly fill the damaged area and restore the integrity and hydrophobicity of the coating. In contrast, particles such as SiO2 and TiO2, when combined with PDMS, often cannot achieve similar self-healing functions due to weak surface chemical properties or unstable structures.

[0044] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0045] 1. Superhydrophobicity is significantly improved: Through the synergistic effect of alkaline etching treatment and nano-hydroxyapatite (HAP) composite suspension, a highly rough micro-nano structure is formed on the wood surface, which significantly improves the water contact angle (up to 153.3°) and has a small rolling angle (less than 5°), showing excellent superhydrophobic properties and is suitable for wood applications in outdoor environments.

[0046] 2. Strong coating stability: After the wood has been subjected to harsh environmental tests such as tape stripping, water shock, chemical corrosion, UV irradiation, and freeze-thaw cycles, the superhydrophobic properties remain stable, and the contact angle has hardly changed significantly. This shows that the coating is firmly bonded to the substrate, can withstand mechanical and chemical damage in a variety of environments, and is suitable for long-term use. After 60 days of outdoor exposure, the water contact angle of the superhydrophobic coating can still be maintained at 152.5°, and the rolling angle is about 6.1°, proving that the coating has good weather resistance and is suitable for long-term outdoor applications.

[0047] 3. Outstanding self-repairing ability: Within the repair temperature range, the super-hydrophobic coating on the wood surface has good self-repairing ability, especially at 100°C. After multiple wear and repair cycles, the water contact angle can still be restored to 142°, and the repair rate is as high as 92.4%, which effectively extends the service life of the coating.

[0048] 4. No adverse effect on mechanical properties: Alkaline etching treatment did not significantly reduce the bending strength and compressive strength of wood, which verified that this modification method not only enhanced the surface properties of wood, but also maintained the original mechanical properties of wood, ensuring the structural safety in practical applications.

[0049] 5. Environmental protection and cost-effectiveness: The composite suspension used in the present invention has low toxicity and simple process, avoiding the need for expensive equipment such as complex vapor deposition, and has good prospects for industrial production while reducing potential harm to the environment and human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a scanning electron micrograph of the hydroxyapatite nanospheres in Example 1;

[0051] Figure 2 This is the water contact angle test diagram of the wood surface coating;

[0052] Figure 3 The data diagram of water contact angle and rolling angle of wood surface coating;

[0053] Figure 4 The three-dimensional contour diagram of the wood surface, a is natural wood, b is wood treated with alkali etching;

[0054] Figure 5 The water contact angle test diagram of wood surface coating under different alkali treatment conditions, a is different sodium hydroxide concentrations, b is different immersion time;

[0055] Figure 6 The water contact angle test diagram of the wood surface coating with different nanoparticles added;

[0056] Figure 7a~f are water contact angle test diagrams of Example 1 after tape stripping, water impact, chemical corrosion, UV irradiation, repeated freezing and thawing, and outdoor exposure, respectively, and g~h are bending strength and compressive strength after alkali treatment, respectively;

[0057] Figure 8 The results of multiple wear-repair experiments of wood super-hydrophobic coating at different temperatures, a~e are the effects of repair temperature on contact angle, f~i are the changes in repair rate, h~i are the repair rate and water contact angle at 100°C respectively;

[0058] Fig. 9 This is the water contact angle test diagram of the coating on the cross section of wood. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0060] Unless otherwise specified, the reagents and materials used in the following examples are commercially available. The polydimethylsiloxane and curing agent used in the following embodiments are SYLGARD TM 184.

[0061] Example 1

[0062] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. The treated wood was then soaked in a 0.5wt% NaOH solution for 2 hours and then taken out. The residual NaOH on the surface of the wood was washed with deionized water and then dried in an oven at 103°C for 6 hours. 0.08g HAP was added to 40g ethyl acetate, followed by 0.8g polydimethylsiloxane prepolymer and 0.08g curing agent, and ultrasonically dispersed for 30 minutes to prepare a composite suspension. Finally, the prepared composite suspension was heated to 1g / cm 2 The amount of the superhydrophobic wood was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and then dried in an oven at 80°C for 1 hour to obtain superhydrophobic wood.

[0063] Example 2

[0064] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. The treated wood was then soaked in a 0.1wt% NaOH solution for 2 hours and then taken out. The residual NaOH on the surface of the wood was washed with deionized water and then dried in an oven at 103°C for 6 hours. 0.08g HAP was added to 40g ethyl acetate, followed by 0.8g polydimethylsiloxane prepolymer and 0.08g curing agent, and ultrasonically dispersed for 30 minutes to prepare a composite suspension. Finally, the prepared composite suspension was heated to 1g / cm 2 The amount of the superhydrophobic wood was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and then dried in an oven at 80°C for 1 hour to obtain superhydrophobic wood.

[0065] Example 3

[0066] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. The treated wood was then soaked in a 1wt% NaOH solution for 2 hours and then taken out. The residual NaOH on the surface of the wood was washed with deionized water and then dried in an oven at 103°C for 6 hours. 0.08g HAP was added to 40g ethyl acetate, followed by 0.8g polydimethylsiloxane prepolymer and 0.08g curing agent, and ultrasonically dispersed for 30 minutes to prepare a composite suspension. Finally, the prepared composite suspension was heated to 1g / cm 2 The amount of the superhydrophobic wood was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and then dried in an oven at 80°C for 1 hour to obtain superhydrophobic wood.

[0067] Example 4

[0068] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. The treated wood was then soaked in a 0.5wt% NaOH solution for 2 hours and then taken out. The residual NaOH on the surface of the wood was washed with deionized water and then dried in an oven at 103°C for 6 hours. 0.08g HAP was added to 48g ethyl acetate, followed by 0.8g polydimethylsiloxane prepolymer and 0.08g curing agent, and ultrasonically dispersed for 30 minutes to prepare a composite suspension. Finally, the prepared composite suspension was heated to 1.2g / cm 2 The amount of the superhydrophobic wood was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and then dried in an oven at 80°C for 1 hour to obtain superhydrophobic wood.

[0069] Example 5

[0070] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. The treated wood was then soaked in a 0.5wt% NaOH solution for 1 hour and then taken out. The residual NaOH on the surface of the wood was washed with deionized water and then dried at room temperature (25°C) for 24 hours for use. 0.08g HAP was added to 32g ethyl acetate, followed by 0.8g polydimethylsiloxane prepolymer and 0.08g curing agent, and ultrasonically dispersed for 30 minutes to prepare a composite suspension. Finally, the prepared composite suspension was heated to 0.8g / cm 2 The amount of the hydrophobic agent was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and the wood was placed at room temperature (25°C) for 12 hours to obtain superhydrophobic wood.

[0071] Comparative Examples 1 to 3

[0072] The technical solutions of Comparative Examples 1 to 3 are similar to those of Example 1, except that Comparative Example 1 (WH-WE-W) is not treated with alkali and does not contain HAP, Comparative Example 2 (WH-EW) is treated with alkali and does not contain HAP, and Comparative Example 3 (H-WE-W) is not treated with alkali and contains HAP.

[0073] Comparative Examples 4-5

[0074] The technical solutions of Comparative Examples 4 to 5 are similar to that of Example 1, except that the concentrations of the NaOH solutions are 3 wt % and 5 wt %, respectively.

[0075] Comparative Examples 6-7

[0076] The technical solutions of Comparative Examples 6 to 7 are similar to those of Example 1, except that the alkali treatment time is 0.5 h and 4 h, respectively.

[0077] Comparative Examples 8 to 9

[0078] The technical solutions of Comparative Examples 8 to 9 are similar to those of Example 1, except that HAP is replaced by SiO2 and TiO2, respectively.

[0079] Detection Methods

[0080] (1) Extreme environment testing

[0081] The super-hydrophobic wood of Example 1 was subjected to tape stripping 30 times (using 3M tape to strip the coating surface), 10L water shock (fixing the sample on a slope with an inclination angle of 45°, and then releasing the water at a distance of 30 cm from the wood sample), soaking in a strong acid and strong base solution for 12 h (immersing the sample surface coating in a strong acid and strong base solution), ultraviolet irradiation for 24 h (placing the sample at a distance of 10 cm from the ultraviolet lamp for irradiation), freeze-thaw cycles 5 times (repeated freezing and thawing of the coating surface), and outdoor exposure for 60 days, and then the water contact angle was tested.

[0082] (2) Coating self-healing test

[0083] After the superhydrophobic wood of Example 1 was subjected to 7 wear-repair cycles (the sample coating was placed downward under 1500CW sandpaper, and a 50g weight was placed on the wood. The wood was pushed to move on the sandpaper surface, vertically moving 5cm and then horizontally moving 5cm, which was recorded as 1 wear cycle; the worn sample was placed in an oven at 100°C and taken out after 1h, which was recorded as 1 wear-repair cycle), the water contact angle was tested.

[0084] (3) Cross-section hydrophobicity test

[0085] The tangential section of the wood was polished with sandpaper and washed with 75% ethanol and pure water. 0.1 g, 0.08 g, 0.53 g, and 0.04 g of HAP were added to 40 g of ethyl acetate, followed by 0.8 g of polydimethylsiloxane prepolymer and 0.08 g of curing agent, and ultrasonically dispersed for 30 min to prepare a composite suspension. Finally, the prepared composite suspension was heated to 1 g / cm 2 The amount of the superhydrophobic wood was sprayed on the polished surface of the wood at a distance of 30 to 50 cm from the wood, and then dried in an oven at 80°C for 1 hour to obtain superhydrophobic wood.

[0086] Analysis

[0087] Depend on Figure 1 It can be seen that the hydroxyapatite nanospheres are spherical, with a diameter of about 10 to 30 nm.

[0088] Figure 2 This is a test diagram of the water contact angle of the wood surface coating in Example 1, and its water contact angle is about 153.3°.

[0089] like Figure 3 As shown, Example 1 was treated with alkali and HAP was added at the same time, and the contact angle of the HEW sample was as high as 153.3°, and the rolling angle was the smallest (4.3°), showing the best hydrophobic performance. Comparative Example 1 was not treated with alkali and no HAP was added. The water contact angle on the surface of the WH-WE-W sample was low (145.3°) and the rolling angle was high, indicating that its hydrophobic performance was poor. Comparative Example 2 was treated with alkali but no HAP was added. Although the water contact angle on the surface of the WH-EW sample was slightly improved (146.8°), the rolling angle was still high. Comparative Example 3 was not treated with alkali but HAP was added, which shows that although the H-WE-W sample with only HAP added improved the water droplet rolling performance, the water contact angle was still lower than that of the HEW sample in Example 1. The above results show that the synergistic effect of alkali treatment and HAP can significantly increase the roughness of the wood surface, increase the surface active sites, and thus greatly enhance its hydrophobicity.

[0090] like Figure 4As shown, the surface of natural wood is relatively smooth and the color distribution is relatively uniform, indicating that the surface has less microstructure and lower average roughness ( Figure 4 a). The wood surface after alkali treatment in Example 6 shows more red areas, representing an increase in surface height differences ( Figure 4 b). Since the alkali treatment partially corrodes the wood surface and forms a rougher microstructure, the wood surface provides more active sites for the attachment of the hydrophobic coating, enhancing the stability and hydrophobic effect of the hydrophobic coating. The average roughness Ra of the natural wood surface is 3.9 μm, and the roughness of the wood surface in Example 3 is greatly increased to 8.5 μm.

[0091] like Figure 5 As shown in a, when the NaOH concentration is 0.1wt%, 0.5wt%, and 1wt% (Examples 1 to 3), the water contact angle is greater than 150°, reaching the super-hydrophobic condition (the test results of Examples 4 to 5 are all greater than 150°). However, when the NaOH concentration is further increased to 3wt% and 5wt%, the contact angle decreases instead. This is because the excessively high concentration of alkaline solution causes excessive corrosion on the wood surface, destroys the appropriate microscopic roughness structure, reduces the active sites, and thus reduces the hydrophobicity. Figure 5 As shown in Figure 2, as the alkali treatment immersion time increases, the water contact angle gradually increases. However, when the immersion time exceeds 2 hours (such as 4 hours in Comparative Example 7), the water contact angle of the prepared wood is 145.5°. When the immersion time of Comparative Example 6 is 0.5 hours, the roughness of the wood surface is insufficient, and the water contact angle of the prepared wood is 147.3°. When the NaOH concentration is too high and the immersion time is not within the appropriate range, the water contact angle of the obtained wood is less than 150°, which does not meet the super-hydrophobic standard.

[0092] like Figure 6As shown, the water contact angle of the coating based on HAP in Example 1 can reach 153.3°, while the water contact angles of the samples containing silicon dioxide (Comparative Example 8) and titanium dioxide (Comparative Example 9) are all less than 150°, and super-hydrophobicity is not achieved. Super-hydrophobicity depends on the micro-nano structure of the material surface to increase the contact angle between water droplets and the surface. HAP can form a more uniform and rougher microstructure on the wood surface, making it almost impossible for water droplets to penetrate into the microscopic gaps, thereby forming a high contact angle. SiO2 and TiO2 themselves have high hydrophilicity. The surface of silicon oxide has a large number of silanol (Si-OH) groups, which can form hydrogen bonds with water molecules, increase the interaction between water and the surface of the material, and thus limit the contact angle of water droplets. TiO2 also has hydrophilic properties at room temperature, especially when exposed to light, the oxidation reaction generated on the surface will enhance this hydrophilicity. Therefore, even if these materials are hydrophobically modified, their inherent hydrophilic properties are still difficult to completely eliminate, affecting the final hydrophobic effect. When the modifier is PDMS, the more active sites on the surface of HAP particles can better combine with PDMS to form a stable hydrophobic coating. For SiO2 and TiO2, the chemical reaction during the combination with PDMS is not as effective as HAP, resulting in reduced stability and hydrophobicity of the hydrophobic layer, ultimately resulting in a smaller contact angle and less hydrophobic performance than expected. In addition, due to the surface energy and the interaction between particles, nanoparticles of SiO2 and TiO2 are prone to agglomeration or uneven distribution, thereby reducing hydrophobicity.

[0093] according to Figure 7 a~f, the preparation method of the present invention not only significantly improves the hydrophobic properties of wood, but also in the face of various harsh environments such as mechanical peeling, water shock, chemical corrosion, ultraviolet light, freeze-thaw cycles and long-term outdoor exposure, the water contact angle has almost no change and remains above 150°. It shows that the super-hydrophobic coating on the surface of the wood has strong adhesion and peeling resistance, is suitable for complex outdoor environments such as heavy rain, long-term sun exposure, alternating hot and cold, and maintains stable performance. After 60 days of exposure to the outdoors, the water contact angle was about 152.5° and the rolling angle was 6.1°. In addition, according to Figure 7 g~h, after alkali etching, the bending strength and compressive strength of the wood did not decrease significantly, which verified that this method would not destroy the mechanical properties of the wood itself and ensured its structural safety in practical applications.

[0094] according to Figure 8a~e, the changes in water contact angle after two repair cycles at 40℃, 60℃, 80℃, 100℃, and 120℃. At lower temperatures (such as 40℃ and 60℃), the water contact angle changes greatly and the repair effect is unstable. At 100℃, the contact angle always remains at a high level (all over 150°), and the contact angle fluctuates less after repair, proving that its repair effect is the best. At 120℃, although the contact angle can be restored in a short period of time, if Figure 8 As shown in Figure g, the wood underwent obvious deformation at this temperature, indicating that the high temperature caused damage to the wood itself and it was difficult to maintain the mechanical properties of the material. Figure 8 Figure f shows the trend of the repair rate at each temperature as the number of repairs increases. It can be seen that the repair rate at 80°C and 100°C remains at a high level, even reaching more than 90% after multiple repair cycles. However, the repair rate is significantly reduced at lower temperatures (such as 40°C) and higher temperatures (such as 120°C). Figure 8 i shows the change in contact angle after seven repairs at 100°C. Although the water contact angle has slightly decreased, it can still maintain a high level, indicating good durability. At 100°C, after seven wear-repair cycles, the water contact angle on the wood surface can still be restored to 142°, and the repair rate reaches 92.4%, showing extremely high self-repair performance ( Figure 8 h). Figure 8 j shows the change in contact angle after wear and repair. At 100°C, the water droplet contact angle drops below 90° after the coating is worn, but the contact angle quickly recovers after repair, approaching the original superhydrophobic level, indicating that the superhydrophobic coating has good self-healing ability.

[0095] according to Fig. 9 , spraying the composite suspension of the present invention on the cross section, when the mass ratio of HAP to PDMS in the composite suspension is 1:8-20, the water contact angle on the wood surface is greater than 150°. When the mass ratio of HAP to PDMS in the composite suspension is 1:10, the hydrophobicity on the wood cross section is the best, and its water contact angle can reach 156.1°.

[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing super-hydrophobic wood, characterized in that: The following steps are involved: S1: alkaline etching treatment of wood; S2: Spraying a composite suspension containing nano-hydroxyapatite, polydimethylsiloxane, ethyl acetate and a curing agent on the wood surface, and obtaining super-hydrophobic wood after curing.

2. The method for preparing super hydrophobic wood according to claim 1, wherein: The mass ratio of ethyl acetate to nano-hydroxyapatite is 400-600:

1.

3. The method for preparing super hydrophobic wood according to claim 1, wherein: In the composite suspension described in S2, the mass ratio of nano-hydroxyapatite to polydimethylsiloxane is 1:8-20.

4. The method for preparing super hydrophobic wood according to claim 1, characterized in that: During the alkali etching treatment in S1, the wood is immersed in an alkali solution with a concentration of 0.1-1 wt%.

5. The method for preparing super hydrophobic wood according to claim 1, wherein: During the alkaline etching treatment in S1, the wood is immersed in an alkaline solution for a period of 0.5 to 4 hours.

6. The method for preparing super hydrophobic wood according to claim 1, characterized in that: The amount of the composite suspension in S2 added to the wood surface is 0.8-1.2 g / cm 2 .

7. The method for preparing super hydrophobic wood according to claim 1, characterized in that: The wood surface described in S2 includes a cross section, a tangential section and a radial section.

8. A super hydrophobic wood, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. The super hydrophobic wood according to claim 8, characterized in that: After being damaged, the superhydrophobic coating can be restored at a temperature above 80°C and below 120°C.

10. A composite suspension, characterized in that: Used to prepare the super-hydrophobic wood according to claim 8, the components include nano-hydroxyapatite, polydimethylsiloxane, ethyl acetate and a curing agent.

Citation Information

Patent Citations

  • A superhydrophobic wood and its preparation method

    CN104924379B

  • Super-hydrophobic wood and preparation method thereof

    CN104924379A

  • Hydroxylapatite overlong nanowire magnetic incombustible paper

    CN108103846A

  • Preparation method of super-hydrophobic hot liquid composite coating

    CN114773946A

  • Superhydrophobic surface and method for forming same

    US20090011222A1